Analysis of Science Teachers’ Difficulties in Implementing Differentiated Learning in the Independent Curriculum at Senior High Schools - Dulhasyim, Ashari Bayu P.; Untajana, Sally E.; Sopacua, Fryan; Sopacua, Venty (Pascasarjana, Mataram University, 2025)
Differentiated learning is an innovative approach aimed at improving instructional effectiveness by tailoring teaching methods and materials to meet students' individual needs. However, most science teachers in West Seram Regency have not yet implemented this approach optimally. Some teachers have even made mistakes in its application and face various significant challenges. This study aims to analyze the difficulties experienced by senior high school science teachers in implementing differentiated learning in accordance with the Merdeka Curriculum. The study involved 30 teachers from 6 senior high schools in the region and employed both quantitative and qualitative descriptive methods using a survey design. Instruments included questionnaires to measure levels of difficulty and interviews to strengthen the data. The results revealed that four out of six schools had not yet implemented differentiated learning effectively, with an average difficulty level reaching 63.3%. The main difficulties included a lack of conceptual understanding, limited resources, and minimal training related to the new curriculum. These findings underscore the need to enhance teachers’ professional capacity through intensive training so that they can design more inclusive and adaptive learning strategies, ultimately improving the quality of education in West Seram Regency.